GAMBARAN INTENSI MAHASISWA KEPERAWATAN DALAM MEMBERIKAN PERTOLONGAN PERTAMA PADA KECELAKAAN LALU LINTAS - Temala, Dewa Ayu Dwi Yaswari; Suindrayasa, I Made; Saputra, Kadek (Coping: Community of Publishing in Nursing, 2023)
Intention is one of the important factors in predicting helping behavior in traffic accidents. Traffic accidents are one of the most common types of accidents that cause losses in terms of mortality and morbidity. The existence of first responders who know the first aid step, and are able and willing to help victims is needed. One of the potential responders is nursing students. This study aims to determine the intentions of nursing students in providing first aid in traffic accidents. This research is a quantitative study with a descriptive research design through an observational approach. Respondents of this study were 111 active students of the Bachelor of Nursing Science and Nursing Profession Study Program, Faculty of Medicine, Udayana University who had passed the emergency nursing course. This study used total sampling. Data collection using the Measure of Intention to Help Road Accident Victim (MIHRAV) questionnaire that has been translated and modified. The results showed that most of the respondents were class of 2019 (59,5%), the majority of respondents were 22 years old (47,7%), female (90,9%), had attended education and training related to first aid in accidents (81,1%), had seen traffic accidents directly (85,6%), and the majority had never helped victims of traffic accidents (55,9%). The majority of respondents had a high intention to provide first aid to traffic accident victims (53,2%).